Extensive Variation in Gene Expression is Revealed in 13 Fertility-Related Genes Using RNA-Seq, ISO-Seq, and CAGE-Seq From Brahman Cattle - Ross, Elizabeth M.; Sanjana, Hari; Nguyen, Loan T.; Cheng, YuanYuan; Moore, Stephen S.; Hayes, Ben J. (Frontiers in Genetics, 2022)
Fertility is a key driver of economic profitability in cattle production. A number of studies have identified genes associated with fertility using GWAS and differential gene expression analysis, however the genes themselves are poorly characterised in cattle. Here we selected thirteen genes from the literature which have previously been shown to have strong evidence for an association with fertility in Brahman cattle (Bos taurus indicus), or closely related breeds. We examine the expression variation of the thirteen genes that are associated with cattle fertility using RNA-seq, CAGE-seq and ISO-seq data from 11 different tissue samples from an adult Brahman cow and a Brahman foetus. Tissues examined include blood, liver, lung, kidney, muscle, spleen, ovary and uterus from the cow, and liver and lung from the foetus. The analysis revealed several novel isoforms including seven from SERPINA7. The use of three expression characterisation methodologies (5’ cap selected ISO-seq, CAGE-seq and RNA-seq) allowed the identification of isoforms that varied in their length of 5’ and 3’ untranslated regions, variation otherwise undetectable (collapsed as degraded RNA) in generic isoform identification pipelines. The combinations of different sequencing technologies allowed us to overcome the limitations of relatively low sequence depth in the ISO-seq data. The lower sequence depth of the ISO-seq data was also reflected in the lack of observed expression of some genes that were observed in the CAGE-seq and RNA-seq data from the same tissue. We identified allele specific expression that was tissue specific in AR, IGF1, SOX9, STAT3, and TAF9B. Finally, we characterised an exon of TAF9B as partially nested within the neighbouring gene Phosphoglycerate kinase 1. As this study only examined two animals, even more transcriptional variation may be present in a genetically diverse population. This analysis reveals the large amount of transcriptional variation within mammalian fertility genes and illuminates the fact that the transcriptional landscape cannot be fully characterised using a single technology alone.